2003
DOI: 10.1046/j.1365-2133.2003.05032.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thickness of photoprotective lipsticks and frequency of reapplication: results from a laboratory test and a field experiment

Abstract: Our investigation shows that photoprotective lipsticks are applied in a much thinner layer than recommended by international standards (2 mg cm(-2)). This results in a significant reduction of the photoprotective capacity. Furthermore, the frequency of application is too low for adequate protection. Therefore, we propose that the sun protection factor (SPF) should be assessed for an area density that reflects the actual usage patterns. As long as the test protocol is not adapted to the reduced area density, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The role of lip photoprotection in decreasing the risk of lip cancer was shown in a study performed with Californian women; those who infrequently applied lip protection (no more than once a day) had twice the risk compared to women who used lip protection more often [13]. Despite this evidence, photoprotection promotion strategies specifically directed to lips are scarce [5,14,15]. Our study is consistent with this, as only 9.3% of the AC patients had ever used lip photoprotection.…”
Section: Discussionsupporting
confidence: 85%
“…The role of lip photoprotection in decreasing the risk of lip cancer was shown in a study performed with Californian women; those who infrequently applied lip protection (no more than once a day) had twice the risk compared to women who used lip protection more often [13]. Despite this evidence, photoprotection promotion strategies specifically directed to lips are scarce [5,14,15]. Our study is consistent with this, as only 9.3% of the AC patients had ever used lip photoprotection.…”
Section: Discussionsupporting
confidence: 85%
“…There is merit in recommending high and ultrahigh SPF photoprotective lipblocks because lower SPF products may not be applied in a thick enough layer and with enough frequency to optimize lip photoprotection. 12 The reason why lower or higher SPF sunscreens and lipblocks are selected and used for skin and lip photoprotection from UVL is not well understood and is worthy of further investigation. It is possible that those selecting higher SPF sunblocks are more concerned about limiting UVL damage, whereas those choosing lower SPF products may still want to tan while avoiding sunburn.…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation all lipsticks were applied onto quartz glass slides as a layer of 1.0±0.1 mg/cm 2 which is only half of the area density (2.0±0.2 mg/cm 2 ) recommended by the COLIPA guidelines to measure the sun protection factor (SPF) of sunscreens (33). We decided to reduce the area density because our own study (34) showed that in practice lipsticks are applied in a much thinner layer than required by the COLIPA guidelines. The application thickness will change the absolute height of the absorbance curve but not its shape.…”
Section: Methodsmentioning
confidence: 99%